Pengaruh Hypnobirthing Terhadap Penurunan Nyeri Pada Ibu Intranatal Kala I - Mayang Wulan; Nuriah Arma; Utary Dwi Listiarini (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
Background: The World Health Organization (WHO) reports that every year morethan 200 million pregnant women, most pregnancies end in the birth of live babies tohealthy mothers, even though in some cases, birth is not a happy event but becomesa comfortable period. They fill with pain, fear, suffering, and even death.Hypnobirthing is carried out for mothers in labor to create calm conditions for themother to reduce tension and anxiety and minimize pain during delivery. This studyaims to determine the effect of hypnobirthing on reducing pain in mothers in the firststage of labor.Method: This research design is quantitative research, where the research designused is Quasi Experiment with Pre test-Post test Design without a control group. Thesample for this research was mothers giving birth in the 1st stage in June-August 2022 at BPS Irawati using a minimum experimental sample size of 15 mothers givingbirth. The sampling technique was purposive sampling. Data analysis by univariateanalysis test, bivariate analysis test Wilcoxon Test.Result: The results of the study, before being given hypnobirthing, nine peopleexperienced unbearable pain, and six people weighed. Whereas the mothers whogave hypnobirthing experienced mild pain, 13 people and two had moderate pain.Based on the results of the Wilcoxon Signed Rank Test calculation, the p-value is0.001.There is an effect of hypnobirthing on reducing birth pain in mothers in the firststage. It recommends that midwives apply hypnobirthing in the care of birthingmothers to reduce labor pain.Keyword: Hypnobirthing, Pain, Intranatal 1st Stage